Influence of Brand Image and Service Quality, and Word of Mouth for Selecting Fertility Clinic - Wenny; Andry, Andry; Arrozi, Muhammad Fachruddin (International Journal of Nursing and Health Services (IJNHS), 2024)
Background: Several factors influence the patient's decision in choosing a hospital such as Brand Image, Service Quality and also from family/friends’ recommendations through Word of Mouth. Objective: The study aimed to analyze the impact of Brand Image and Service Quality on fertility clinic selection decisions with Word of Mouth as an intervening variable. Method: A cross-sectional study was applied in this study. We involved 99 respondents using the purposive sampling technique. The statistically analysis using the path analysis regression model. Result: This study found that Brand Image had no significant influence on the Word of Mouth and did not affect the Clinical Selection. Word of mouth did not significantly mediate the influence of the Brand Image on the Clinic Selection Decision. Conclusion: specific aspects of brand image and service quality such as success rates, patient care, and facilities. Recommendation: hospitals should improve all dimensions of service quality in order to improve the good patients experience. The future study could add some factors associated with intention to use the fertility clinic